Arrangement of nuclear structures is not transmitted through mitosis but is identical in sister cells - Orlova, Darya Yu; Stixová, Lenka; Kozubek, Stanislav; Gierman, Hinco J; Šustáčková, Gabriela; Chernyshev, Andrei V; Medvedev, Ruslan N; Legartová, Soňa; Versteeg, Rogier; Matula, Pavel; Stoklasa, Roman; Bártová, Eva (Journal of cellular biochemistry, 2012)
Although it is well known that chromosomes are non-randomly organized during interphase, it is not completely clear whether higher-order chromatin structure is transmitted from mother to daughter cells. Therefore, we addressed the question of how chromatin is rearranged during interphase and whether heterochromatin pattern is transmitted after mitosis. We additionally tested the similarity of chromatin arrangement in sister interphase nuclei. We noticed a very active cell rotation during interphase, especially when histone hyperacetylation was induced or transcription was inhibited. This natural phenomenon can influence the analysis of nuclear arrangement. Using photoconversion of Dendra2-tagged core histone H4 we showed that the distribution of chromatin in daughter interphase nuclei differed from that in mother cells. Similarly, the nuclear distribution of heterochromatin protein 1β (HP1β) was not completely identical in mother and daughter cells. However, identity between mother and daughter cells was in many cases evidenced by nucleolar composition. Moreover, morphology of nucleoli, HP1β protein, Cajal bodies, chromosome territories, and gene transcripts were identical in sister cell nuclei. We conclude that the arrangement of interphase chromatin is not transmitted through mitosis, but the nuclear pattern is identical in naturally synchronized sister cells. It is also necessary to take into account the possibility that cell rotation and the degree of chromatin condensation during functionally specific cell cycle phases might influence our view of nuclear architecture.
Keywords: histony; Chromosomal Proteins, Non-Histone; RNA, Messenger; Cell Line; Fluorescent Dyes; fluorescenční mikroskopie; Cell Nucleolus; heterochromatin; Protein Synthesis Inhibitors; Mitosis; Histone Deacetylase Inhibitors; Hydroxamic Acids; Interphase; daktinomycin; Coiled Bodies; interfáze; inhibitory syntézy proteinů; Dactinomycin; fotochemické procesy; Animals; lidé; Microscopy, Fluorescence; Photochemical Processes; inhibitory histondeacetylas; Heterochromatin; Humans; zvířata; kyseliny hydroxamové; fluorescenční barviva; myši; buněčné linie; chromozomální proteiny, nehistonové; Histones; mitóza; Cajalova tělíska; Mice; messenger RNA; buněčné jadérko